Mitochondrial Imbalance as a New Approach to the Study of Fibromyalgia - Martínez-Lara A (Dove Medical Press, 2020)
Antonio Martínez-Lara,1 Ana María Moreno-Fernández,2 Maripaz Jiménez-Guerrero,1 Claudia Díaz-López,1 Manuel De-Miguel,2 David Cotán,1,3 José Antonio Sánchez-Alcázar3 1Pronacera Therapeutics S.L., Seville, Spain; 2Departamento de Citología e Histología Normal y Patológica, Facultad de Medicina, Universidad de Sevilla, Seville, Spain; 3Centro Andaluz de Biología del Desarrollo (CABD-CSIC-Universidad Pablo de Olavide), Seville 41013, SpainCorrespondence: David Cotán Tel +34 615 41 26 42Email david.cotan@hotmail.comBackground: Fibromyalgia (FM) is a common chronic pain disease, whose pathogenic mechanism still remains elusive. Oxidative stress markers and impaired bioenergetics homeostasis have been proposed as relevant events in the pathogenesis of the disease. Hence, the aim of the study is to analyse the potential biomarkers of mitochondrial imbalance in FM patients along with coenzyme Q10 (CoQ10) as a possible treatment.Methods: The symptomatology of patients was recorded with an adaption of the Fibromyalgia Impact Questionnaire (FIQ). Mitochondrial imbalance was tested from blood extraction and serum isolation in 33 patients diagnosed with FM and 30 healthy controls. Western blot and HPLC techniques were performed to study the different parameters. Finally, bioinformatic analysis of machine learning was performed to predict possible associations of results.Results: CoQ10 parameter did not show evidence to be a good marker of the disease, as the values are not significantly different between control and patient groups (Student’s t-test, CI 95%). For this reason, the focus of the study changed into the ratio between mitochondrial mass and autophagy levels. The bioinformatics analysis showed a possible association between this ratio and patients’ symptomatology. Finally, the effects of coenzyme Q10 as a potential treatment for the disease were different within patients, and its efficacy may be related to the initial mitochondrial status. However, there is no statistical significance due to limitations within the sample size.Conclusion: Our study supports the hypothesis that an imbalance in mitochondrial homeostasis is involved in the FM pathogenesis. However, whether the increase in oxidative stress is the result of mitochondrial imbalance or the cause of this disease remains an open question. The measurement of this imbalance might be used as a preliminary biomarker for the diagnosis and follow-up of patients with FM, and even for the evaluation of the effects of the different antioxidants therapies.Keywords: fibromyalgia, diagnosis, mitochondria, chronic pain